Perlindungan Konsumen Terkait Wanprestasi terhadap Bagasi Penumpang yang Hilang oleh Perusahaan Penerbangan - Afriadi, Dedi; Rusli, Benni; Mairul, Mairul (Innovative: Journal Of Social Science Research, 2024)
Protection of consumer rights is very important for both the use of goods and services, one of which is in aviation. Loss or damage to passenger baggage is something that happens quite often in the world of Indonesian aviation. Therefore, the aim of this research is to find out how the law regulates the rights and obligations of both consumers and airlines and what forms of legal protection exist for consumers for losses suffered based on Law no. 8 of 1999 concerning consumer protection, a form of responsibility for airlines based on Law No. 1 of 2009 concerning Aviation. This research uses a normative legal research method using secondary data consisting of primary, secondary and tertiary legal materials and the approach method used is a normative legal approach which focuses the study by viewing law as a complete system encompassing a set of legal principles, norms and norms. legal norms, and legal rules, both written and unwritten, related to consumer protection regarding defaults regarding lost passenger baggage by airline companies. Where the results of the research are that there are differences in the regulations used between consumers and airlines in terms of compensation, airlines are based on PERMENHUB No. 77 of 2011 while consumers are based on the Consumer Protection Law.